POST TRAUMATIC STRESS DISORDER AMONG SURVIVORS OF AFGHAN TORTURE AND CONCENTRATION CAMPS - Nazir, Zahid; Said, Samina; Mufti, Khalid A. (Journal of Ayub Medical College Abbottabad, 1999)
Thirty Afghan refugees who had survived torture and concentration camps experience were subjected to thorough psychiatric search. All of them met the DSM-III R Criteria for post- traumatic Stress Disorder. Their main symptoms were avoidance of the past recall, intrusive thoughts and nightmares that were persistent. These findings give cross-cultural validation of post-traumatic stress syndrome in general while with a difference that (i). Younger patients of our study group showed better prognosis and minimum suicidal tendencies, (ii). Duration of stay in concentration Camps was significantly less as compared to Western studies.